2021
DOI: 10.1097/ccm.0000000000005363
|View full text |Cite
|
Sign up to set email alerts
|

Vasopressor Initiation Within 1 Hour of Fluid Loading Is Associated With Increased Mortality in Septic Shock Patients: Analysis of National Registry Data*

Abstract: OBJECTIVES: To investigate whether administration of a vasopressor within 1 hour of first fluid loading affected mortality and organ dysfunction in septic shock patients. DESIGN: Prospective, multicenter, observational study. SETTING: Sixteen tertiary or university hospitals in the Republic of Korea. PATIENTS: Patients with septic shock (n = 415) were classified into early and late groups according to whether the vasopressor was initiated within 1 hour of the first resuscitative fluid load. Early (n = 14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 29 publications
1
32
0
Order By: Relevance
“…Previous studies have suggested the potential benefits of early vasopressor use [ 8 - 12 , 22 , 23 ], but there is no precise index for the timing of vasopressor administration during initial sepsis management. Moreover, we could not conclude that prompt vasopressor use would improve outcomes in all hypotensive patients with suspected sepsis [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have suggested the potential benefits of early vasopressor use [ 8 - 12 , 22 , 23 ], but there is no precise index for the timing of vasopressor administration during initial sepsis management. Moreover, we could not conclude that prompt vasopressor use would improve outcomes in all hypotensive patients with suspected sepsis [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Early vasopressor use might allow faster achievement of the mean arterial pressure target. However, there are also traditional concerns regarding the impact of early vasopressor use [ 14 , 28 ]. Vasopressors may have potentially harmful effects in masking inadequate fluid resuscitation, and vasoconstriction may induce tissue hypoperfusion and organ dysfunction [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While both groups received more than 30 mL/kg of fluid, a greater volume was administered to the late vasopressor group within 6 h of shock identification (33.4 ± 21.0 vs. 38.0 ± 15.7 mL/kg; p = 0.046). Vasopressor dosing is not reported in this study, limiting the comparison to previously mentioned publication [ 28 ]. Future studies are needed to assess the relationship between fluid and vasopressor initiation and restrictive fluid strategies in sepsis.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, all these analyses in the CHASERS study were adjusted for severity of illness factors such as APACHE III score, comorbidities, and other resuscitative interventions. In contrast, a recently published prospective, multicenter, observational study classified patients into early and late vasopressor groups based on vasopressor timing in relation to fluid resuscitation [ 28 ]. In this propensity-matched analysis, there was a greater risk of 28-day mortality when vasopressor initiation occurred within 1 h after fluid bolus administration (47.7% vs. 33.6%; p = 0.013).…”
Section: Introductionmentioning
confidence: 99%